벼줄무늬잎마름병 신규 저항성 보유 유전자원 탐색 - 이샛별(Sais-Beul Lee); 허연재(Yeon-Jae Hur); 조준현(Jun-Hyun Cho); 이지윤(Ji-Yoon Lee); 권영호(Yeongho Kwon); 조수민(Sumin Jo); 신동진(Dongjin Shin); 이종희(Jong-Hee Lee); 김태헌(Tae- Heon Kim); 강주원(Ju-Won Kang); 박노봉(No-Bong Park); 송유천(You-Cheon Song); et al. (Korean journal of breeding, 2019)
Rice stripe virus (RSV) is one of the major constraints in rice production which is transmitted by the small brown plant hopper, Laodelphax striatellus. Identifying new resistance genes from diverse sources is important for rice breeding programs to enhance resistance level and/or to overcome the breakdown of resistance genes. This study was conducted to identify novel source of resistance against RSV. We used 5 RSV resistant varieties which do not harbor Stv-b i . Presence of known genes on RSV resistance was identified with InDel7 marker for Stv-b i , two Indel (Sid primer set) markers for Stv-b, and DNA sequence analysis for OsSOT1. We revealed that two varieties, 02428 (IT236925) and Tung Ting Wan Hien 1 are the novel resistance sources of RSV. KCI Citation Count: 0